The role of viruses in the induction and progression of asthma - Papadopoulos, N. G.; Johnston, S. L. (Curr Allergy Asthma Rep, 2001)
Viral respiratory infections have been related to asthma in several ways. It is well established that viral common colds precipitate exacerbations of asthma. Severe bronchiolitis in early life is related to subsequent wheezing and therefore may represent a marker of susceptibility to asthma; alternatively, it could be involved in the initiation of the disease. Finally, it is possible that some infections may protect from the development of asthma and allergies by promoting a type-1 host response. However, whether respiratory or other viruses could mediate such a protective effect is debated. The design and implementation of novel anti- or proviral strategies targeting asthma depends on the resolution of these questions. This review presents current evidence on the epidemiologic correlations and proposed mechanisms for the involvement of viral infections in the development and progression of asthma.
Keywords: Animals Asthma Disease Progression Humans Respiratory Tract Infections